The Gross and net produce of all the branches of the revenue under the management of the commissioners of His Majesty's Customs in England together with an adjustment of the net produce with the payments into the Exchequer annually from Christmas 1710 to which are prefixed the underwritten acco[unts] viz[t] : 1. The yearly payments into the receipt of Exchequer on all the several branches of the customs from Michaelmas 1679 to Christmas 1710. 2. The payments into the Exchequer for prohibited uncustomed and forfeited goods yearly from Christmas 1701 - Great Britain. Customs Establishment (1679)
Ledger of His Majesty's Customs in England from 1679 to 1766.
Cover title: The gross and net produce of the Customs annually from Christmas 1710.
Manuscript reference no.: NLA RB Strongroom.
Keywords: Great Britain. -- Treasury; Tariff -- England -- Early works to 1800.; England -- Commerce